Fostering the development of the entrepreneurial university: how PhD students create new ventures and are involved in technology transfer activities. Issue 5 (4th May 2022) - Battaglia, Daniele; Cucino, Valentina; Paolucci, Emilio; Piccaluga, Andrea
ABSTRACT: The literature on Entrepreneurial University has emphasised the importance of encouraging and supporting the entrepreneurial intent of students, both PhDs and undergraduates. However, more research is needed about how PhD students can be supported in their entrepreneurial and technology transfer initiatives. This study seeks to contribute to this field by investigating how the entrepreneurial intent and entrepreneurial education of PhDs can impact their creation of new ventures and their involvement in technology transfer activities. With this objective, we use a unique dataset of 396 PhD students enrolled in Italian universities. The results show that higher levels of entrepreneurial intention of PhDs lead to a higher number of new ventures and higher involvement in TT activities. Furthermore, our findings also show that entrepreneurship education encourages PhDs to create new ventures only through increased entrepreneurial intention. Finally, education on technology transfer directly pushes them to be more involved in commercialisation activities.